Microgrids formed by renewable energy integration into power grids pose electrical protection challenges. (December 2016) - Akhtar, Zohaib; Saqib, Muhammad Asghar
Abstract: System parameters of a microgrid change in its two operating modes primarily due to output current limitation of PWM based inverters connected with renewable energy sources. The unavailability of an appropriate protection scheme, which must be compatible with both modes of a microgrid operation, is a major problem in the implementation of a microgrid. Two important properties of the microgrid components are peer-to-peer, and plug-and-play. It means that there is no component like a master controller which is critical for the operation of a system, and a distributed-generation unit can be installed at any location in a microgrid. These properties further complicate the protection of a microgrid. This paper reports the MATLAB/SIMULINK model of a microgrid along with the models of the conventional protection schemes and renewable energy distributed-generation resources. Malfunctioning in the conventional protection schemes in islanding mode is identified and models of newly proposed protection schemes are developed. Different types of faults are simulated in all the protection zones of the system and the system parameters are analysed to identify the possible fault detection methods. Based on the simulation results, a protection scheme is recommended that can meet the protection standards such as selectivity, co-ordination and reliability. Highlights: The paper presents MATLAB model of a microgrid formed by renewable-energy sources. Different protection relays, used in a microgrid, are modelled in MATLAB/Simulink. Conventional protection techniques are analysed for microgrids' application. Conventional protection schemes do not work correctly in a microgrid. A protection scheme has been designed that works satisfactorily in microgrids.